Colonization of the Intestinal Tract of the Polyphagous Pest Spodoptera littoralis with the GFP-Tagged Indigenous Gut Bacterium Enterococcus mundtii - Teh, Beng-Soon; Apel, Johanna; Shao, Yongqi; Boland, Wilhelm (Frontiers in Microbiology, 2016)
The alkaline gut of Lepidopterans plays a crucial role in shaping communities of bacteria. Enterococcus mundtii has emerged as one of the predominant gut microorganisms in the gastrointestinal tract of the major agricultural pest, Spodoptera littoralis. Therefore, it was selected as a model bacterium to study its adaptation to harsh alkaline gut conditions in its host insect throughout different stages of development (larvae, pupae, adults and eggs). To date, the mechanism of bacterial survival in insects’ intestinal tract has been unknown. Therefore, we have engineered a GFP-tagged species of bacteria, E. mundtii, to track how it colonizes the intestine of S. littoralis. Three promoters of different strengths were used to control the expression of GFP in E. mundtii. The promoter ermB was the most effective, exhibiting the highest GFP fluorescence intensity, and hence was chosen as our main construct. Our data show that the engineered fluorescent bacteria survived and proliferated in the intestinal tract of the insect at all life stages for up to the second generation following ingestion.